Properties characterization of binary composite hydrogels of gellan gum and Aloe vera blended at different ratios, pH, and solid contents - HERNÁNDEZ-BRIONES, Verónica Guadalupe; GONZÁLEZ-GARCÍA, Raúl; PÉREZ-MARTÍNEZ, Jaime David; GRAJALES-LAGUNES, Alicia; ABUD-ARCHILA, Miguel; RUIZ-CABRERA, Angel (Food Science and Technology, 2023)
Composite hydrogels based on natural polymers with manufactured properties according to the desired application for the food industry are currently significant. Thus, this study aimed to study the association of low acyl gellan gum (LAGG) and Aloe vera gel (AVG) for composite hydrogel creation by controlling pH (1, 4, 7), solid content (0.25, 0.50, 0.75 w/v), and polymer ratio (66:33, 50:50, and 33:66 LAGG/AVG). Hydrogels were prepared by physical crosslinking, diluting the required amount of LAGG at 90 °C, followed by AVG at 60 °C, and storing at 4 °C. The study involved the analysis of zeta potential (x), water holding capacity (WHC), hardness, storage modulus ( ), loss modulus ( ), and the phase transition temperature ( ) of hydrogels. The corresponding values of x, WHC, hardness, , and of produced hydrogels were found to be in the ranges of -23.3±1.52 to 6.3±0.25 mV; 4.6±0.22 to 98.9±0.16%; 0.4±0.15 to 14.3±0.81 N; 16,100 to 89,700 Pa; and 22 to 46 °C. Statistical analysis (p<0.05) showed that pH, solid content, and polymer ratio significantly influenced hydrogels' functional properties. However, as a general trend, the pH*solid content interaction was among the most critical factors influencing response variables.